The Influence of Tax, Foreign Ownership and Company Size on the Application of Transfer Pricing in Manufacturing Companies Listed on IDX during 2013-2017 - Yulia, Aida; Hayati, Nurul; Daud, Rulfah M. (International Journal of Economics and Financial Issues, 2019)
The objective of this research is to examine the effects of tax, foreign iownership, and firm size on the application of transferi pricing in the manufacturing companies listed on Indonesia Stock Exchange during 2013-2017. This study is hypothesis-testing research by using purposive sampling method with a total of 110 samples of data. Secondary data in the form of financial statements with the year ended 31 December were obtained from the Indonesia Stock Exchange. Logistic regression was used to test the hypotheses. The results of thisi research show that tax, foreign ownership, andi firm size simultaneously influences the application of transfer pricing. Meanwhile partially tax was found to significantly influence the application of transfer pricing. In addition foreign ownership and firm sizei does not influence the application of transfer pricing. Keywords: Transfer pricing, Tax, Foreign ownership, Firm size. JEL Classifications: H2, F21, G30 DOI: https://doi.org/10.32479/ijefi.7640